Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cjce.23566
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized bacterial cellulose nanowhiskers as long‐lasting drug nanocarrier for antibiotics and anticancer drugs

Abstract: A nano drug carrier based on sustainable and biocompatible nanocellulose was developed for use in prolonged drug releases. The grafting of β-cyclodextrin (βCD) on bacterial cellulose nanowhiskers (BCNC) using citric acid (CA) as a green linker was performed. This led to the formation of functionalized BCNC-grafted-βCD (BCNC-g-βCD). Broad-spectrum antibiotic Ciprofloxacin (CIP) and anticancer drugs Doxorubicin (DOX) and Paclitaxel (PTX) were used as model drugs. These model drugs were conjugated to BCNC-g-βCD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Some antidiabetic drugs were evaluated as anticancer and cytotoxic agents, which showed positive results. [ 26,27 ] Although metformin is a first‐line drug for type 2 diabetes, due to its mitochondrial effects, it is also under investigation as an anticancer agent. Our previous studies have indicated that some herbal medicines used traditionally for both cancer and diabetes, including Capparis spinose, Teucrium polium , and Prosopis farcta , induced a significant cytotoxicity in HT‐29 cells and regulated the mitochondrial function (i.e., mitochondrial membrane potential collapse and ROS overproduction) and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Some antidiabetic drugs were evaluated as anticancer and cytotoxic agents, which showed positive results. [ 26,27 ] Although metformin is a first‐line drug for type 2 diabetes, due to its mitochondrial effects, it is also under investigation as an anticancer agent. Our previous studies have indicated that some herbal medicines used traditionally for both cancer and diabetes, including Capparis spinose, Teucrium polium , and Prosopis farcta , induced a significant cytotoxicity in HT‐29 cells and regulated the mitochondrial function (i.e., mitochondrial membrane potential collapse and ROS overproduction) and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For all of the drug‐loaded nanocarriers, the observed slow drug release results were fitted with a zero‐order kinetic model. The output of this study approved the potential of this method for preparation of the efficient systems with reducing frequent daily dosing 197 …”
Section: Ca‐based Ddssmentioning
confidence: 66%
“…The output of this study approved the potential of this method for preparation of the efficient systems with reducing frequent daily dosing. 197 Guan et al designed the CA-modified poly(lactic acid)-poly(L-lysine) (PLA-PLL)/FA to evaluate its performance as DDS for drug delivery. In the system, micellar poly(lactic acid) (PLA) was employed as the hydrophobic portion, and poly(L-lysine) (PLL) was used as the hydrophilic portion.…”
Section: Ca-modified/functionalized Platformsmentioning
confidence: 99%
“…Moreover, promoted drug release profiles were pragmatic in an acidic pH of 6.4 at 37°C, which mimics the tumour environment. The obtained observations demonstrate versatile medical applications for the obtained nanocarriers in localized and long‐lasting drug delivery …”
mentioning
confidence: 73%